Етнолінгвістичний характер народної етимології та табу - Руснак, Наталія Олександрівна (Чернівці–Сучава: БДМУ, 2021)
Natalia Rusnak. Ethnolinguistic nature of folk etymology and taboo. The purpose of the article is to analyze the Ukrainian nominations due to the internal form of the word. The names of literary language and vernacular on the basis of ethnolinguistic phenomena – folk etymology and taboos are involved in the analysis. The relevence of the study is due to the need to clarify ethnolinguistic phenomena associated with ambivalent tendencies – the vivid imagery of the word and its concealment and reproduction in linguistic concepts. Research methods. In the article as the main general scientific methods of analysis and synthesis are used, as well as linguistic – descriptive, structural and comparative and historical methods. Conclusions. For ethnolinguistics the phenomenon of folk etymology is important, which testifies the desire of speakers to explain the name, illustrates the subconscious attempt of native speakers to poetize the word, to inspire the word with poetry. In folk speech etymology motivates primarily toponyms and nicknames of people. Under the influence of folk etymology the literary language and folk words change their sound composition. Ethnolinguistic character has such a phenomenon as taboo: the word "hides" the internal form. During the Christmas holidays the speakers of the Bukovinian dialects had a taboo on the pronunciation of the word poppy. Taboo was widely used in folk birth rites. Euphemisms are associated with the phenomenon of taboos. In vernacular the word “devil” has many “substitutes”. Periphrases are close to euphemisms. In literary language there are established periphrases which emphasize the feature of the concept.
Ethnolinguistic nature of folk etymology and taboo
Keywords: етнолінгвістика; народна етиимологія; внутрішня форма слова; табу; евфемізм; перефраза; семантичний словотвір